The choroid plexuses and their impact on developmental neurogenesis - Johansson, Pia A. (Frontiers in Neuroscience, 2014)
During brain development the neural stem cells are regulated by both intrinsic and extrinsic sources. One site of origin of extrinsic regulation is the developing choroid plexuses, primely situated inside the cerebral ventricles. The choroid plexuses are very active in terms of both secretion and barrier function as soon as they appear during development and control the production and contents of cerebrospinal fluid (CSF). This suggests that regulated secretion of signaling molecules from the choroid plexuses into CSF can regulate neural stem cell behavior (as they are in direct contact with CSF) and thereby neurogenesis and brain development. Here, choroid plexus development, particularly with regards to molecular regulation and specification, is reviewed. This is followed by a review and discussion of the role of the developing choroid plexuses in brain development. In particular, recent evidence suggests a region-specific reciprocal regulation between choroid plexuses and the neural stem cells. This is accomplished by site-specific secretion of signaling molecules from the different choroid plexuses into CSF, as well as brain region specific competence of the neural stem cells to respond to the signaling molecules present in CSF. In conclusion, although in its infancy, the field of choroid plexus regulation of neurogenesis has already and will likely continue to shed new light on our understanding of the control and fine-tuning of overall brain development.